E-Module Development of Linear Programs Based on Students' Conceptual Understanding - Lestari, Fransiska Dwi; Syahbana, Ali; Retta, Allen Marga (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
The purpose of this study is to create an E-Module based on conceptual understanding of linear programming that is valid, practical, and understands the potential effects of E-Modules. The Research and Development (RD) method was used in this study. This study employs the ADDIE model development procedure, which consists of five stages: analysis, design, development, implementation, and evaluation. The E-Module is declared "valid" based on the assessments given by three validators with four aspects assessed, namely content feasibility, presentation feasibility, language feasibility, and graphic feasibility, with a total percentage of 79.8 percent. The E-Module was regarded "highly practical" based on the results of student response surveys in the small and large groups, which received 83.8 percent and 81.5 percent, respectively. Based on the findings of the teacher response questionnaire, the E-Module was declared "highly practical" with a score of 92 percent. Based on the student learning outcomes test, the e-module is determined to have a "good" potential effect with a score of 66.7 percent.Penelitian ini bertujuan untuk menghasilkan E-Modul berbasis pemahaman konsep pada materi program linear yang valid, praktis dan mengetahui efek potensial E-Modul. Jenis penelitian ini adalah penelitian Research and Development (RD). Penelitian ini mengggunakan prosedur pengembangan model ADDIE yang terdiri dari lima tahapan yaitu Analysis, Design, Development, Implementation, dan Evaluation. Hasil dari penelitian ini adalah E-Modul dinyatakan “valid” berdasarkan penilaian yang diberikan oleh tiga validator dengan empat aspek yang dinilai yaitu kelayakan isi, kelayakan penyajian, kelayakan bahasa, dan kelayakan kegrafisan dengan jumlah persentase sebesar 79,8%. E-Modul dinyatakan “sangat praktis” berdasarkan hasil angket respon peserta didik pada kelompok kecil (Small Group) dan kelompok besar yang masing-masing mendapat persentase sebesar 83,8% dan 81,5%. Serta E-Modul dinyatakan “sangat praktis” berdasarkan hasil angket respon guru dengan persentase sebesar 92%.  E-modul dinyatakan memiliki efek potensial “baik” berdasarkan tes hasil belajar peserta didik yang dengan persentase sebesar 66,7%.